Ethnoscience of Local Wisdom and Environmental Conservation Practices among Indigenous Madurese Communities: A Study in Pamekasan and Bangkalan: Kajian Etnosains dalam Kearifan lokal Madura (Pamekasan dan Bangkalan) Analisis Pengetahuan Konservasi Masyarakat Adat - Indah Maya Sofa; Mistianah Mistianah (SEARCH: Science Education Research Journal, 2026)
This study examines the local wisdom of the Madurese community in Pamekasan and Bangkalan Regencies, which has been preserved as an integral part of tradition and spiritual values. Local knowledge serves as a guiding framework for the management of both terrestrial and marine environments, contributing to environmental conservation. This research aims to analyze indigenous knowledge based on local conservation concepts and to explore its potential as a resource for biology education. A qualitative descriptive approach was employed, utilizing field study methods. Data were collected through observation, interviews, and documentation involving communities that actively practice local wisdom. Data analysis was conducted to identify the forms and meanings of local knowledge related to conservation practices. The results specifically indicate that: (1) customary regulations govern the management of water springs, limiting exploitation and ensuring the sustainability of water discharge; (2) traditional agricultural practices implement cropping patterns and land-use strategies that maintain soil fertility; and (3) prohibitive values and customary rituals function as social mechanisms for preserving environmental sustainability. These findings reflect the integration of biological concepts such as ecosystem balance, resource conservation, and sustainability. Therefore, Madurese local wisdom demonstrates strong relevance as an ethnoscience-based resource for biology learning, particularly in linking scientific concepts with real-life contexts.